Environmental Friendly Crush-Magnetic Separation Technology for Recycling Metal-Plated Plastics from End-of-Life Vehicles - Xue, Mianqiang; Li, Jia; Xu, Zhenming (Environmental science & technology, 2012)
Metal-plated plastics (MPP), which are important from the standpoint of aesthetics or even performance, are increasingly employed in a wide variety of situations in the automotive industry. Serious environmental problems will be caused if they are not treated appropriately. Therefore, recycling of MPP is an important subject not only for resource recycling but also for environmental protection. This work represents a novel attempt to deal with the MPP. A self-designed hammer crusher was used to liberate coatings from the plastic substrate. The size distribution of particles was analyzed and described by the Rosin-Rammler function model. The optimum retaining time of materials in the crusher is 3 min. By this time, the liberation rate of the materials can reach 87.3%. When the density of the suspension is 31 250 g/m3, the performance of liberation is the best. Two-step magnetic separation was adopted to avoid excessive crushing and to guarantee the quality of products. Concerning both the separation efficiency and grade of products, the optimum rotational speed of the magnetic separator is 50–70 rpm. On the basis of the above studies about the liberating and separating behavior of the materials, a continuous recycling system (the technology of crush-magnetic separation) is developed. This recycling system provides a feasible method for recycling MPP efficiently, economically, and environmentally.